Desenvolvimento de protótipo para prevenção de lesão por pressão : D-PRELP - Azevedo, Maiana Souza (2019)
Introduction: Fostering the development of technologies that assist in the prevention of pressure injuries in elderly patients is becoming increasingly important because, as this population grows, solutions that promote an improvement in the quality of life of these individuals become fundamental. In addition, pressure injuries correspond to a financial, psychological and social burden on hospitals, patients and family members who live with this problem. Thus, the development of low cost products that can effectively assist in the prevention of pressure injuries is essential. Objective: To develop a low cost prototype of a pressure injury prevention device in the elderly. Methodology: Design study with methodological approach based on Altshuller's Theory of Inventive Problem Solving (TRIZ). The steps and tools offered by the theory for prototype design were applied, such as the ideal final result (IFR), the inventive principles and the resource analysis. Results: The design of a low cost prototype that uses special foams and vibration as mechanisms to promote the maintenance of interface pressure below 32mmHg in calcaneal was developed. Product: A prototype of a pressure injury prevention device denoted as D-PRELP. Conclusion: D-PRELP proves to be a developing support surface with potential to be produced on an industrial scale for future testing and validation. The dissemination of knowledge about product design methodologies in nursing enables the resolution of inventive health problems, promoting the idealization of applicable, viable and low cost artifacts